THE EFFECT OF TAMSULOSIN 0.4 MG ADMINISTRATION TOWARDS ALTERATION OF PROSTATE SPECIFIC ANTIGEN (PSA) LEVELS IN BENIGN PROSTATIC HYPERPLASIA (BPH) PATIENTS IN PADANG CITY - Asril, Fadly; MYH, Etriyel; Yunir, Peri Eriad (Indonesian Journal of Urology, 2024)
Objective: This study aims to determine the effect of tamsulosin administration on alteration in PSA levels in BPH patients in Padang. Material & Methods: This study employed an analytical method with a prospective cohort design. The research was conducted at M. Djamil General Hospital, BMC Hospital, Hermina Hospital, and Semen Padang Hospital in August - December 2022. Sampling was carried out by consecutive sampling. Results: At the end of the study, there were 23 patients with BPH. The mean age was 67.5 ± 7.7, which most of them having good education. Patients were mostly self-employed. The highest IPSS score is the severe stage. The PSA levels before and after tamsulosin administration were 1.7 ± 0.9 ng/ml and 1.6 ± 0.8 ng/ml, respectively. Bivariate analysis showed that tamsulosin administration affects PSA levels in benign prostatic hyperplasia patients in Padang. Conclusion: There is an effect of tamsulosin administration on PSA levels. Keywords: Benign prostatic hyperplasia, tamsulosin, prostate-specific antigen.